BRACKISH WATER FOR IRRIGATION: IV. EFFECTS ON YIELD OF MAIZE (ZEA MAYS L.) AND SATURATED HYDRAULIC CONDUCTIVITY OF SOIL - Abid, Muhammad; Anwar-ul-Hassan; Ghafoor, Abdul (Journal of Research (Science), 2003)
The experiment was conducted to investigate the effect of brackish water irrigation on fresh biomass yield of maize variety Agati-72 and saturated hydraulic conductivity (HC) of silty clay loam soil. Total 20 treatment combinations having different ECiw (0.65, 2.0, 4.0, 6.0 and 7.35 dS m-1), SARiw [3.95, 9.65, 18.0, 26.35 and 32.04 (mmol L-1)1/2] and RSC (0.65, 2.0, 4.0, 6.0 and 7.35 mmolc L-1) were applied to 30 cm x 68 cm undisturbed and disturbed soil columns. Results indicated that biomass yield of maize decreased with an increase in ECiw from 0.65 to 7.35 dS m-1 at coded “0” levels of SARiw and RSC in undisturbed soil. The maize tolerated ECiw up to 2.0 dS m-1 at coded “0” levels of SARiw and RSC in disturbed soil. The SARiw up to 18.0 did not affect the yield of crop at coded “0” levels of ECiw (4.0 dS m-1) and RSC (4.0 mmolc L-1) in both soil conditions. The RSC up to 2.0 and 4.0 mmolc L-1 did not affect the yield at coded “0” levels of SARiw and ECiw for the undisturbed and disturbed soils, respectively. The increase in HC was 48% in undisturbed and 54% in disturbed soils with ECiw 7.35 dS m-1 over ECiw 0.65 dS m-1 coded “0” levels of ECiw and RSC. The HC decreased with SARiw and RSC at coded “0” levels of ECiw and RSC; ECiw and SARiw in both the soil columns.